1970
DOI: 10.1039/j19700003068
|View full text |Cite
|
Sign up to set email alerts
|

Metal–metal bonding in co-ordination complexes. Part X. Preparation, spectroscopic properties, and crystal structure of the cis-isomer of di-µ-carbonyl-dicarbonyldi-π-cyclopentadienyldi-iron (Fe–Fe)

Abstract: The cis-isomer of di-cL-carbonyl-dicarbonyldi-rr-cyclopentadienyldi-iron has been isolated by low-temperature crystallisation and its structure determined by a single-crystal X-ray analysis. The crystals are monoclinic, a = 8.880(2), b = 12.301 (3). c = 13.1 40(3) 8, p = 108.64(1)". The space group is P2Jc with Z = 4. After leastsquares refinement with over 1500 observations R is 0.051. The i.r. spectrum of the complex has been measured in the ranges 200-1 000 and 1600-2000 cm.-l and assignments have been sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0
2

Year Published

1992
1992
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(42 citation statements)
references
References 0 publications
5
35
0
2
Order By: Relevance
“…The X-ray and neutron diffraction studies [7][8][9] showed that I has a centrosymmetric structure in the solid phase with two bridging and two terminal carbonyl groups (trans-bridged form). Low-temperature crystallization made possible isolation of the cis form [10]. However, only the trans-bridged structure of crystalline II was detected by the X-ray and neutron diffraction methods [11,12].…”
Section: Experimental Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The X-ray and neutron diffraction studies [7][8][9] showed that I has a centrosymmetric structure in the solid phase with two bridging and two terminal carbonyl groups (trans-bridged form). Low-temperature crystallization made possible isolation of the cis form [10]. However, only the trans-bridged structure of crystalline II was detected by the X-ray and neutron diffraction methods [11,12].…”
Section: Experimental Datamentioning
confidence: 99%
“…X-ray study of I together with sublimation experiments and low-temperature crystallization led to conclusion that the cis form is thermodynamically less stable [7,10]. 1 H-NMR spectra of I dissolved in C 6 D 6 -CS 2 showed, however, that the cis-bridged isomer is by 4.2 kJ/mol more stable than the trans one, with the energy barrier of transbridged-I´non-bridged-I interconversion of about 54.3 kJ/mol [18].…”
Section: Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…IV sind ausgew ählte Bindungslängen und -winkel enthalten. 4 ist ein Derivat der cis-Form der A usgangsverbindung 3 [15], in der eine der term inalen C arbonylgruppen durch den aus dem D iphosphet 1 entstandenen H e terocyclus über eine F e-P -B indung substituiert ist. Das R um pfm olekül ist durch diese Substitution na hezu unverändert geblieben: Die F e -C A bstände in der term inalen C O -G ruppe betragen im M it tel 173,2 pm, w ährend die verbrückten C arbonyl gruppen 187,9 pm von den Fe-Atom en entfernt sind.…”
Section: Kristallstruktur Vonunclassified
“…Das R um pfm olekül ist durch diese Substitution na hezu unverändert geblieben: Die F e -C A bstände in der term inalen C O -G ruppe betragen im M it tel 173,2 pm, w ährend die verbrückten C arbonyl gruppen 187,9 pm von den Fe-Atom en entfernt sind. Der D iederw inkel der beiden Fe2C-Ebenen in der Fe2(C O )2-Einheit, der in der A usgangsver bindung 164° beträgt [15], ist um 8° verkleinert. D ieser Wert von 156° w ird in einem aryl-und alkylsubstituierten Bis[(dicarbonyl)(//5 -cyclopentadienyl)eisen]-K om plex gefunden [16], mit einem Triphenylphosphit-Substituenten beträgt er 159° [17J.…”
Section: Kristallstruktur Vonunclassified